2020
DOI: 10.1140/epjc/s10052-020-8279-x
|View full text |Cite
|
Sign up to set email alerts
|

Statistical methods applied to the search of sterile neutrinos

Abstract: The frequentist statistical methods applied to search for short-baseline neutrino oscillations induced by a sterile neutrino with mass at the eV scale are reviewed and compared. The comparison is performed under limit setting and signal discovery scenarios, considering both when an oscillation would enhance the neutrino interaction rate in the detector and when it would reduce it. The sensitivity of the experiments and the confidence regions extracted for specific data sets change considerably according to whi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 39 publications
3
37
0
Order By: Relevance
“…4 we will compute the distribution of T for more realistic configurations and will always confirm rather large deviations from a χ 2distribution. This suggests that reliable statements about significance and confidence levels require explicit Monte-Carlo simulations, in agreement with previous results [27,28]. We will demonstrate this explicitly using the recent results from Neutrino-4 in Sect.…”
Section: General Remarkssupporting
confidence: 86%
See 2 more Smart Citations
“…4 we will compute the distribution of T for more realistic configurations and will always confirm rather large deviations from a χ 2distribution. This suggests that reliable statements about significance and confidence levels require explicit Monte-Carlo simulations, in agreement with previous results [27,28]. We will demonstrate this explicitly using the recent results from Neutrino-4 in Sect.…”
Section: General Remarkssupporting
confidence: 86%
“…1 leads to a strong non-linear behavior. Therefore, significant deviations of the distribution of T from a χ 2 -distribution are expected a priori, see also [27,31]. A recent review discussing the applicability of Wilk's theorem can be found in Ref.…”
Section: General Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Before discussing our results, let us point out that the determination of the sensitivity to sterile neutrinos from oscillations is non-trivial from the statistical point of view. In particular, the results obtained under the assumption that Wilks' theorem [95] applies may differ from the ones obtained via Monte Carlo simulation [43,[96][97][98]. The sensitivity contours in this work have however been computed under the assumption that Wilks' theorem applies, in order to ease the comparison with previous literature.…”
Section: Sterile Neutrinosmentioning
confidence: 98%
“…A common source of error in statistical analysis is to assume that the test statistic follows a χ 2 distribution with mean equal to the degrees of freedom (dof's) according to Wilks' theorem [105]. This is often not correct and can lead to significantly incorrect results [75,106,107], as it has been pointed out recently in the context of short baseline neutrino oscillations [108][109][110][111][112][113][114] and for the determinations of the leptonic CP phase [115][116][117][118]. In fact for low number of events per bin the test statistic is not expected to follow a χ 2 distribution as in this case the necessary condition to fulfill Wilks' theorem that enough data is observed is not met (see for example [107]).…”
mentioning
confidence: 99%